2015
DOI: 10.4034/pboci.2015.151.25
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sense of Coherence and Dental Caries Experience in Adolescents

Abstract: Objective: To analyze the association between sense of coherence and dental caries experience in adolescents. Material and Methods: A cross-sectional study was conducted with 100 adolescents aged 11 to 15 years old who were attending the Debora Feijo State School in the city of Recife (Brazil). Information was collected on sociodemographic data -age, gender, school failure and number of residents per home. Sense of coherence (SOC) was evaluated using the SOC-13 questionnaire and the dental caries experience wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…Other studies highlighted the protective role of SOC by reducing the impact caused by adverse situations, such as illness or even war. With regard to oral health, few studies have assessed the relationship between SOC and dental caries in the infant population, and the findings are in line with the present study [Bonanato et al, 2009a;Lyra et al, 2015;Viswanath and Krishna, 2015]. One study demonstrated that adolescents whose mothers had a higher SOC score had lower levels of dental caries and gingival bleeding and were less likely to visit the dentist in urgent need than those whose mothers had lower SOC scores [Freire et al, 2001].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Other studies highlighted the protective role of SOC by reducing the impact caused by adverse situations, such as illness or even war. With regard to oral health, few studies have assessed the relationship between SOC and dental caries in the infant population, and the findings are in line with the present study [Bonanato et al, 2009a;Lyra et al, 2015;Viswanath and Krishna, 2015]. One study demonstrated that adolescents whose mothers had a higher SOC score had lower levels of dental caries and gingival bleeding and were less likely to visit the dentist in urgent need than those whose mothers had lower SOC scores [Freire et al, 2001].…”
Section: Discussionsupporting
confidence: 76%
“…The literature has shown that oral and general health status are related to social and psychological issues [Freire Bonanato et al, 2009a;Coutinho and Heimer, 2014;Lyra et al, 2015;Viswanath and Krishna, 2015]. An integrative review of the literature showed that several studies have shown that a strong SOC was associated with different health behaviors, such as improved oral hygiene, conscious use of medicines, not taking up smoking, lower consumption of alcohol, and the more frequent practice of physical activities [Coutinho and Heimer, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the 35 selected studies are presented according to the age group and type of study. Table presents the main characteristics of the 7 cohort studies: 5 involving children and 2 involving early adolescents; one case–control study in children; and 27 cross‐sectional studies: 14 involving children and 13 involving early adolescents. The sample sizes varied from 32 to 981 in children and from 100 to 2014 in adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies in children and adolescents were conducted in schools. The protective psychosocial factors investigated were as follows: health locus of control (12 studies), self‐efficacy (11 studies), sense of coherence (10 studies), social support (5 studies), self‐esteem (3 studies), and social network (2 studies). Coping, resilience, family functioning, self‐concept, and optimism were assessed in one study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation